Abortion among married young women: findings from a community-based study in Rajasthan and Uttar Pradesh, India - A. J. Francis Zavier; K. G. Santhya; Shireen J. Jejeebhoy (J. Biosoc. Sci., 2020)
Abortion service provision has changed noticeably in the recent past and medication abortion currently accounts for four-fifths of all induced abortions taking place in India. How these changes have modified abortion experiences among young women - a group known to be more disadvantaged than adult women - remains unanswered. This paper fills this gap and examines the experiences of married young abortion seekers, including pre-abortion decision-making, abortion seeking and experiences of the procedure, and post-abortion complications. Data were drawn from a community-based survey of 4952 married young women aged 15-24 years conducted in Uttar Pradesh and Rajasthan in 2015. The study focused on 166 young women who had an induced abortion in the two years before the survey, and used descriptive statistics to describe their abortion experiences. Seventy-four per cent of abortion seekers had relied on medication abortion and 47% had obtained it over the counter without a physician's prescription. Moreover, 90% accessed abortion services from private facilities, including drug sellers. A small proportion (4%) had undergone abortion in the second trimester of pregnancy. At the same time, 13% reported multiple abortion attempts; 17% underwent dilation and curettage; and 52% experienced self-reported complications, including 5% who experienced moderate to severe complications. The findings call for greater attention to providing contraceptive counselling and services to married young women, ensuring abortion services in public health facilities and exploring mechanisms to improve drug sellers' knowledge and practices in providing medication abortion.
Keywords: Abortion; Postabortion care; Menstrual regulation; Quality of care; Maternal health services